Review of William T. Dargan. 2006. Lining Out the Word: Dr. Watts Hymn Singing in the Music of Black Americans. Berkeley and Los Angeles: University of California Press - Miller, Kiri (Current Musicology, 2008)
William T. Dargan’s methodologically diverse and elegantly written book engages with numerous musical genres, historical moments, and modes of social analysis, but it revolves around a single core idea: that we can trace the development of all African American music back to the productive tensions between lined-out hymnody and the ring shout. Dargan argues that the “lining out-ring shout continuum” provides the key to understanding the historical provenance, functional efficacy, and cultural distinctiveness of black spirituals, the blues, jazz, R &B, and rap. A thesis of such all-encompassing scope can only be supported through considerable speculative theorizing, as Dargan acknowledges; he states at the outset that Lining Out the Word will not lead to “semantic certainty” about the traditions and theories under discussion, but will remain “open ended and inconclusive”. Nevertheless, the depth and complexity of his historical and musical analysis have a significant persuasive impact over the course of the book, gradually returning the reader’s ear through repeated explication of a particular theoretical vocabulary.